Employers’ Expectations for Recruitment Decision of Fresh Graduates During the Covid-19 Pandemic - Jaya GANESAN; Sin Kiat KOH; Kavitha RAMAN (Communications of International Proceedings, 2021)
This research study in progress aims to identify the employability skills that affect the recruitment decision of employers towards fresh graduates using Maxwell et al model. The study is very relevant and significant during Covid-19 pandemic in the Malaysian context. The research framework depicts eight specific employability skills that act as exogenous variables while recruitment decision representing the only endogenous variable in the study. A total of total 39 measurement items were constructed from nine constructs (including endogenous variable). A quantitative approach will be adopted to accomplish the purpose of the research and a self -administered questionnaire will be used to collect data from 200 employers. The findings of this research aim to provide significant insights to the key stakeholders such as graduates, employers, and higher education institutions. Overall, this study contributes by discussing the implications towards society both theoretically and practically by empirically testing the research framework. Although the study is carried out during the Covid - 19 outbreak, the findings are still applicable in the post pandemic since COVID-19 accelerates the fourth industrial revolution, driving human capital more reliant on technology and consider the structural shifts of relationship with the environment.
Keywords: COVID-19; Employability Skills; Fresh Graduates; Employers’ Expectations.